Constructing Neuron-like Structured NiS2/MOF Composites with Enhanced Regulation of Electron Transport and Active Sites for Oxygen Evolution - Yanli Guo; Di Zhou; Yanyan Huang; Xiaolong Song; Wei He (Molecules)
Constructing fast electron transfer pathways and abundant electro-active sites is an effective strategy to improve the oxygen evolution reaction (OER) performance of catalysts. Herein, structural engineering and dual-phase engineering were employed to construct a NiS2 nanoparticle-encapsulated MOF configured with a pseudo-neuronal structure (NiS2/MOF/HT). It was found that the pseudo-neuronal structure, constructed with a carbon nanohorn (CNH) and carbon nanotube (CNT), provided fast electron transfer pathways and abundant exposed active sites. Moreover, the NiS2/MOF/HT composite obtained via partial vulcanization not only inherited the pseudo-neuronal structure but also prevented the aggregation and growth of NiS2 particles. NiS2/MOF composites provide various active sites. With the combination of the promotion of electronic transfer and enrichment of electro-active sites (NiS2, MOF), NiS2/MOF/HT showed excellent performance, whose overpotential at 25 mA cm−2 was reduced by 19.5% compared with MOF/HT.